Morphological and Physiological Development of Pyricularia oryzae Isolates from North-western Region of Sarawak on Different Media under Laboratory Conditions Laboratory Conditions - Elissa stella, Rafael; Yeo, Freddy Kuok San; Nor Ain, Hussin; Vu Thanh, Tu Anh; Ang, Poh Sim; Ewe, Zhang Hua; Lai, Lee San (2023)
Rice blast (causal agent: Pyricularia oryzae) is an important disease of rice in Sarawak. Understanding the pathogen’s morphological characteristics, genetic diversity and pathogenicity is important. Having a suitable medium for culturing and maintaining P. oryzae is important to ensure the availability of inoculum or materials under laboratory conditions. Oatmeal agar (OMA) and potato dextrose agar (PDA) are common media used for growing P. oryzae. OMA allows better mycelial growth and better sporulation as compared to PDA. There are also other alternatives such as fresh rice leaf agar and rice straw agar. Although OMA seems to be the best medium, unfortunately the opaqueness of the medium causes difficulty in observing the morphology and growth of mycelia. In addition, it is known that different isolates of P. oryzae will respond differently to different media. This study aims to identify the best media for culturing and maintaining P. oryzae isolates from Sarawak. A total of 14 P. oryzae isolates were characterised for their morphological characteristics, growth rate and sporulation rate using seven growing media. These 14 isolates included seven newly identified isolates in this study and seven isolates from a previous study, which were verified using internal transcribed spacer DNA sequence. The colony surface of the 14 P. oryzae isolates varied on different growing media. The pigmentation of colony surface varied from different shades of grey, translucent light brown, white and colourless. Pyricularia oryzae isolates grew better on OMA and PDA, while OMA was the best for sporulation. These two media can be recommended for culturing and maintaining different P. oryzae isolates under laboratory conditions.